Pengaruh Penerapan Standar Akuntansi Pemerintah (SAP) terhadap Kualitas Laporan Keuangan Melalui Kompetensi Pegawai: Pada Badan Kependudukan dan Keluarga Berencana Nasional - Iis Nurliani; Fanlia Prima Jaya; Akhmad Aspiannor (Pajak dan Manajemen Keuangan, 2025)
The purpose of study This is For know influence Implementation Standard Accountancy Government in a way significant to quality report finance in the Agency BKKBN Government; for know influence SAP implementation in general significant to competence employees at the agency Population and Family Agency government National Planning; For know influence SAP implementation in general significant to Quality Report Finance through Competence Employees at the Agency BKKBN Government. Samples taken use formula slovin so that obtained as many as 77 respondents in filling questionnaire. Data analysis methods used is Structural Equation Model with using SmartPLS Software version 3.0. Research result show that (1) Variable SAP implementation has an impact in a way significant to Quality Report Finance in Institutions BKKBN Government, things This show that the more Good SAP implementation then quality Report Finance in Institutions Population and Family Agency Government National planning is also increasing good. (2) Variable SAP implementation has an impact in a way significant to competence employees at the agency BKKBN Government. (3) The implementation of SAP has an impact to Quality Report Finance through Competence Employee , thing This prove that SAP implementation with existence competence employee as variable moderation so can more increase quality report finance Because competence employee become matter fundamental in carry out the implementation of SAP.